(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Concrete is a mixture of cement, natural sand, coarse aggregate and water. Nowadays, the most concrete mixture contains supplementary cementitious material, which forms part of the cementitious component. These materials are by-products from other processes according to the industrial wastes. The benefits of supplementary cementitious material are their ability to show cementitious property after replacement of a certain amount of cement, thus cost reduces in using Portland cement. The fast growth in industrialization has resulted in tons and tons of by-product or waste materials, which can be used as supplementary cementitious material such as Ground-granulated blast-furnace slag, fly ash, silica fume, steel slag etc. Further be noted that use of the by-products not only helps to utilize these waste materials but enhances the properties of concrete in fresh and hydrated states also. The Iron industries produce an enormous quantity of blast furnace slag (B.F.S) as by–product, which is a non– biodegradable waste material from that only a insignificant percentage of it is used by cement industries to manufacture cement. In this study, Blast Furnace Slag from industries has been utilized to find its suitability as cement in concrete making. This topic also deals with the advantages and disadvantages of slag being used in concrete. Replacing some portion of cement with slag would lead to moderately large environmental benefits. In this study it is observed that blast furnace slag could be used as alternative construction material. In the present examination, cement concrete has good strength and workability by using ground blast furnace slag as a replacement for cement. The M45 grade of concrete was prepared and examined at the hardened stage. Then different mixes were prepared containing 0%, 43%, 53%, and 63% as partial replacement of cement with ground blast furnace slag in different combinations were used to examine the strength properties.Tests had been conducted for result of slump, compressive strength, flexural strength, splitting tensile strength, rebound hammer , abrasion and acid attack.